Anthropogenic modifications to a barrier island influence Bonnethead (Sphyrna tiburo) movements in the northern Gulf of Mexico. Issue 1 (December 2015) - Kroetz, Andrea; Powers, Sean; Drymon, J.; Park, Kyeong
Abstract Background Barrier islands are dynamic features of the northern Gulf of Mexico that are affected by natural processes and more frequently, anthropogenic disturbances. In addition to providing a barrier from storms, these islands offer habitat for many marine species. In an effort to prevent oiling of the Alabama coastline following the Deepwater Horizon oil spill, an artificial rock-rubble berm was constructed in 2010 to reconnect two portions of Dauphin Island, a northern Gulf of Mexico barrier island that was separated during Hurricane Katrina. An acoustic array established prior to the closure of "Katrina Cut" was used to investigate the potential effect of this anthropogenic alteration on the movement patterns of acoustically tagged Bonnetheads (Sphyrna tiburo ). Results Across the entire acoustic array, the largest proportion of detections occurred on receivers before construction at Katrina Cut (0.55), followed by the period after the construction (0.25), and the period during the construction (0.20). Focusing on the area near Katrina Cut, the two hydrophones in this area had the highest proportion of detections before construction (0.10), followed by the period during construction (0.02), and then the period after construction and closure of Katrina Cut (<0.01). The post-closure location of highest activity for Bonnetheads shifted westward following the closure of Katrina Cut. Salinity values from a hydrographic model were higher at the Katrina Cut location in 2010 when the cut was open compared to 2011 and 2012 when the cut was closed, a potential explanation for the observed changes in Bonnethead distribution. Conclusions Fluctuations in salinity post-closure of Katrina Cut may effect Bonnethead movements, although other factors, including seasonal migrations and/or the redistribution of their preferred prey, may also be important. Regardless of the mechanism, this rapid shift in distribution of Bonnetheads highlights the potential effect of anthropogenic activities on sharks using coastal environments.